New Century – ‘New Essays’? - Lisak-Gębala, Dobrawa (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
This article constitutes an attempt at organising the non-conservative tendencies in Polish essays published in the 21st century, which apply to themes, the lowering of the tone, and forms of writing. One major stream is travel writing, which focuses not on the Mediterranean legacy, but on the ‘second world’: long-disadvantaged provincial areas. Many essayists abandon the traditional topic of books and works of art, and turn to ‘reading’ the animal world, the plant world, and the world of ordinary objects. The essay has also become a tool for introducing polarisation between that which is mainstream and that which is marginal and concerns minorities. The fact of choosing a non-traditional topic often entails a non-canonical cognitive attitude, which translates into experiments within the area of the form of expression. The author of this article argues that all those innovations can be accommodated by the flexible convention of the essay as a genre which, in principle, is supposed to constitute an artistic cognitive experiment.